2020
DOI: 10.3390/ijms21239053
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Regulation of Copper Homeostasis in the Male Gonad during the Process of Spermatogenesis

Abstract: Owing to its redox properties, copper is a cofactor of enzymes that catalyze reactions in fundamental metabolic processes. However, copper–oxygen interaction, which is a source of toxic oxygen radicals generated by the Fenton reaction, makes copper a doubled-edged-sword in an oxygen environment. Among the microelements influencing male fertility, copper plays a special role because both copper deficiency and overload in the gonads worsen spermatozoa quality and disturb reproductive function in mammals. Male ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 98 publications
0
16
0
1
Order By: Relevance
“…The Cu ion entry into cells is mediated by Cu transporters (CTR), and 80% of Cu ion is transported into the cell by CTR1, which is encoded by Slc31a1 gene (Ogórek et al 2017 ). The intracellular Cu ions are supplied to SOD1 and metallothionein (MT), and excessive Cu ions will bind to the ATOX1 protein and then be transported to ATP7A and ATP7B, which can transport Cu ions to outside the cell or into the blood, respectively (Herman et al 2020 ). The upregulated expression of the testicular copper transporter gene indicated that the concentrations of Cu in the testicular cells was beyond the range of tolerance in testicular cells; for that, Cu transporter gene expression was elevated in order to maintain testicular cell homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…The Cu ion entry into cells is mediated by Cu transporters (CTR), and 80% of Cu ion is transported into the cell by CTR1, which is encoded by Slc31a1 gene (Ogórek et al 2017 ). The intracellular Cu ions are supplied to SOD1 and metallothionein (MT), and excessive Cu ions will bind to the ATOX1 protein and then be transported to ATP7A and ATP7B, which can transport Cu ions to outside the cell or into the blood, respectively (Herman et al 2020 ). The upregulated expression of the testicular copper transporter gene indicated that the concentrations of Cu in the testicular cells was beyond the range of tolerance in testicular cells; for that, Cu transporter gene expression was elevated in order to maintain testicular cell homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study [ 33 ] reported the presence of small amounts of these substances in the interstitial tissue of the testes and the adverse effects in the germ. Moreover, the high quantity of unsaturated fatty acids in the germ cell membranes made the germ cell more vulnerable to oxidative stress caused by the presence of an excessive amount of copper [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is important to note that the majority of cellular Cu is bound by cellular constituents and only a small fraction is free Cu for exchange. For example, about 90% of Cu in the circulation is bound by ceruloplasmin and the other 10% is bound by albumin, histidine, GSH, and transferrin [81,82]. At the intracellular level, in the entire process of Cu(I) transport system, from hCtr1 to the ATPases, Cu(I) movements involve directly coordinate transfers between donor and recipient molecules without metal dissociation.…”
Section: Enhanced Cddp Cell-killing Activity Through Upregulation Of Hctr1 Expressionmentioning
confidence: 99%